Taekwondo exercises for women improve quality of life, physical self-defence skills, and psychological resilience - Yıkılmaz, Ahmet; Yılmaz, Coşkun; Çiçekli, Atıf; Eryılmaz, Önder; Budak, Cemalettin; Uyar, Musa; Ceylan, Tülay; Güler, Özkan; Şahin, Fatma Neşe (Frontiers in Psychology, 2025)
BackgroundThe extant research on Taekwondo has focused primarily on the physiological effects of training, with limited interest in psychological resilience, self-defence and quality of life levels. The present study examined the effects of Taekwondo exercises on psychological resilience, self-defence and quality of life levels in healthy female subjects.MethodsThe present study comprised 30 healthy, sedentary female subjects. The subjects were randomly divided into two groups: one group participated in Taekwondo training (TG), while the other group served as the control group (CG). The sample sizes for both the TG and CG groups were 15. The TT group underwent conventional Taekwondo instruction, while the CG group maintained their habitual routine and refrained from sporting pursuits. The Brief Psychological Resilience Scale, the Physical Self-Defence Scale for Women, and the SF-12 Quality of Life Scale were administered before and after the six-week training period.ResultsThe 6-week Taekwondo training programme led to significant improvements in both physical health (PH) (p = 0.049) and mental health (MH) (p < 0.01) scores in female participants. It did not produce a significant change in psychological resilience (PR) scores (p > 0.05). It produced significant improvements in self-defence against simple physical attacks (SP) (p = 0.004) and self-defence against dangerous physical attacks (DP) (p = 0.041) scores.ConclusionThe positive effects of Taekwondo training on psychological resilience, physical self-defence and quality of life levels have been demonstrated in healthy female subjects. This study provides valuable insights into the impact of Taekwondo exercises on psychological resilience, physical self-defence and quality of life levels. The findings of this study can guide future intervention and programme design in the context of sports psychology.